Structure-Based Hybridization, Microwave Prompted Synthesis and Biological Evaluation of Novel 4-(2-Fluoro-4-Nitrophenyl)morpholine Derivatives - Cebeci, Yildiz U.; Demirbas, Neslihan; Ozdemir, Serap Basoglu; Bayrak, Hacer; Demirbas, Ahmet; Aksakal, Fatma; Karaoglu, Sengul Alpay (Letters in Organic Chemistry, 2018)
1,3,4-oxadiazole-2-thiole 6 was obtained from 4-(2-fluoro-4-nitrophenyl)morpholine (2) by the reduction of its nitro group and the sequential treatment of the resulting amine with ethyl bromoacetate, hydrazine hydrate, and carbon disulfide. The treatment of hydrazide 5 with isothiocyanates produced the corresponding carbothioamides 10a,b. The synthesis of triazoles 11a,b was achieved by intramolecular cyclisation of carbothioamides 10 in basic media. On the other hand, the cyclocondensation of the same carbothioamides with ethyl bromoacetate generated the corresponding 1,3- thiazolidinones 12a,b. The synthesis of the fluoroquinolone or β-lactam hybrids 16-18 was carried out by the reaction of compounds 6, 11 and 12 with the corresponding amines in the presence of formaldehyde. The sequential treatment of triazoles 11a,b with 2-halo-1-(halophenyl)ethenones, NaBH4 and substituted benzylhalides afforded conazole analogues 15a-f. The one-pot four-component synthesis of arylidene rhodanine derivatives 19a-d was achieved under conventional or microwave irradiation conditions. Molecular docking calculations were performed in order to predict binding affinities and noncovalent interactions between enzyme-inhibitor complexes at the molecular level. Docking results were in good agreement with the experimental findings on α-glucosidase and urease inhibitory effects of the compounds. Higher binding affinity values and much more interactions were observed for active compounds in contrary to inactive ones. The synthesized compounds were screened for their antimicrobial and enzyme inhibition activities, and nine of them containing a fluoroquinolone unit exhibited excellent antimicrobial activity on the test microorganisms.
Keywords: 1; 2; 4-triazole